Digital Information Service Portal to ASABRI Participants Batam Branch Office - Dea Mita; Suyono Saputro (ConCEPt - Conference on Community Engagement Project, 2023)
Justified the implementation of internships at ASABRI companies is carried out to analyze problems that occur in companies engaged in this insurance sector, especially in terms of implementing digitalization. The method used in collecting information is by observing and interviewing ASABRI employees directly by visiting the ASABRI office. Problems were found, namely, ASABRI participants often lacked in fulfilling the requirements because they did not get optimal information and it was difficult to access information about claims because they had to come to ASABRI's office. because this is often an obstacle, therefore it is designed to use the platform as a container to accommodate all information related to insurance claims. there are many free websites that can be used as media and in this project linktree was chosen as the media, this project was named the ASABRI information service portal. With the creation of this portal, it is hoped that the company will continue to innovate which can facilitate the continuity of activities that occur within the company.